Wan Azizah is back-up candidate - Povera, Adib; Shazwani, Ili (New Sunday Times, 2014)
PARTI Keadilan Rakyat(PKR) de facto leader Datuk Seri Anwar Ibrahim claimed that his wife, Datuk Seri Dr Wan Azizah Ismail, filed her nomination papers to defend the president's post in the party as part of their backup plan should he be disqualified from the race.